2003
DOI: 10.1046/j.1365-2249.2003.02098.x
|View full text |Cite
|
Sign up to set email alerts
|

Cellular responses to cytomegalovirus in immunosuppressed patients: circulating CD8+ T cells recognizing CMVpp65 are present but display functional impairment

Abstract: SUMMARYThe availability of tetrameric complexes of HLA class I molecules folded with immunodominant peptides makes it possible to utilize flow cytometry for rapid and highly specific visualization of virus specific CD8 + T cells. An alternate technique is to incubate whole blood with specific antigens and to subsequently detect and characterize responding T cells (e.g. by performing intracellular staining of interferon-gamma). By using an HLA-A2 tetramer construct folded with the same immunodominant CMV-peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
1
1

Year Published

2003
2003
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(41 citation statements)
references
References 31 publications
1
38
1
1
Order By: Relevance
“…[6][7][8] Others have shown that the frequency and the absolute number of CMV-specific CD8 þ T cells were similar in patients receiving corticosteroids and those who didn't, while the CMV-specific CD8 þ T cells showed decreased cytokine production. 10,11 Our result was consistent with the latter observation that while the number of CMV-specific CTL does not decrease significantly with corticosteroid therapy, IFN-g production of CMV-specific CTL is severely suppressed. Therefore, concomitant assessment of T-cell function is essential in patients after HSCT, especially in those who are receiving corticosteroid therapy.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…[6][7][8] Others have shown that the frequency and the absolute number of CMV-specific CD8 þ T cells were similar in patients receiving corticosteroids and those who didn't, while the CMV-specific CD8 þ T cells showed decreased cytokine production. 10,11 Our result was consistent with the latter observation that while the number of CMV-specific CTL does not decrease significantly with corticosteroid therapy, IFN-g production of CMV-specific CTL is severely suppressed. Therefore, concomitant assessment of T-cell function is essential in patients after HSCT, especially in those who are receiving corticosteroid therapy.…”
Section: Discussionsupporting
confidence: 81%
“…For this purpose, tetramer-based monitoring of CMV-specific cytotoxic T-cells (CTL) has been widely performed in patients with an HLA-A02 or HLA-B07 serotype. [3][4][5][6][7][8][9][10][11] Some of the results have demonstrated that the reconstitution of CMV-specific CTL as evaluated by quantitative tetramer to levels 410-20/ml is adequate for protection against CMV infection. [5][6][7] However, some patients with CMV-specific CTL above this level still experience CMV reactivation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Probable reasons for this are as follows: i) melanoma patients are much older than volunteers and have high anti-CMV antibody titers, and ii) CTL killing activity was not impaired in the melanoma patients shown in Fig. 6, in contrast to a report that CMV-specific CTLs in immunosuppressive patients showed a decreased functional response to CMV-peptide (24). Our previous report (25) that autologous DC-mediated stimulated CTLs against HLA-A24 melanoma peptide cocktail showed less potent killing activity than healthy volunteers might demonstrate the greater immunogenicity of CMVspecific CTL epitopes.…”
Section: Discussioncontrasting
confidence: 45%
“…Here, the use of corticosteroids impaired these functions in a dose-dependent way. In addition, the combined use of cytokine flow cytometry and class I HLA multimers has revealed that steroid treatment reduces the cytokine-producing fraction within the CMV-specific CD8 1 T cells (42,47). The combined analysis of these studies and our results show that the reduction of CMV-specific T cells in number and function, as an unavoidable effect of immunosuppression to control alloreactivity, will pose SCT recipients at an increased risk of CMV reactivation.…”
Section: And Cd8mentioning
confidence: 57%